Evaluation Of Medicine Procurement Policies On Health Administration And Medicine Demand at X Community Health Center, Deli Serdang Regency In 2025 - Meirizal Jefrinaldi; Romauli Anna Teresia Marbun; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: The 2020–2024 health development agenda emphasizes strengthening primary health services and the utilization of technology, making drug availability an important indicator of service quality. Proper drug management through planning, procurement, distribution, and stock control—supported by competent human resources, adequate funding, and reliable information systems, is essential to prevent stockouts and ensure service continuity. Objective: To analyze and evaluate drug procurement policies in relation to health administration and drug demand at X Public Health Center, Deli Serdang Regency, in 2025 using a qualitative approach. Methods: This study employed a qualitative research design aimed at analyzing and evaluating drug procurement policies and their impact on health administration and drug demand at X Public Health Center, Deli Serdang Regency, in 2025. Results: The findings indicate that drug management is supported by structured policies, competent personnel, relatively adequate though limited budgets, and the use of SIMO, which improves data accuracy. However, policy flexibility and system reliability still need improvement. The procurement process has followed the stages of planning, submission, and distribution with fairly good interdepartmental coordination. Remaining challenges include delays in distribution, slow financial administration processes, and discrepancies between physical stock and system records. Overall, drug procurement has had a positive impact on health administration and service fulfillment, as reflected by relatively stable drug availability. Nevertheless, improvements in procurement speed, supply accuracy, and e-logistics system stability are still required to optimize service quality. Conclusion: Drug management and procurement have been implemented relatively well, supported by structured policies, competent personnel, budget allocation, and the SIMO system, resulting in relatively stable drug availability. However, challenges remain in distribution delays, financial administration, stock discrepancies, and e-logistics system stability, which need to be addressed to further enhance service quality.